Respiratory burst of turbot (Scophthalmus maximus) macrophages in response to experimental infection with viral haemorrhagic septicaemia virus (VHSV) - Tafalla, Carolina; Novoa, Beatriz (Fish & Shellfish Immunology, 2001)
8 páginas, 4 figuras This research was supported by grant MAR 96-1775 from the Comisión Interministerial de Ciencia y Tecnología (CICYT). Peer reviewed